2020
DOI: 10.3892/mmr.2020.11347
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating CREBBP inhibits proliferation and cell cycle progression and induces daunorubicin resistance in leukemia cells

Abstract: Low expression levels of CREB-binding protein (CREBBP) have been demonstrated to be associated with high minimal residual disease at the end of induction therapy and adverse long-term outcomes in pediatric patients with acute lymphoblastic leukemia (ALL). However, the effect of low CREBBP expression on the prognosis of ALL has not yet been investigated. In the present study, CREBBP was downregulated and overexpressed in ALL cell lines (Jurkat and Reh). Sensitivity to chemotherapy and cell proliferation activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…IKZF1 deletion is a critical poor prognostic biomarker in ALL ( 41 ), the mutation of which drives normal lymphocytes to develop into leukemia ( 42 ).It was reported that HSCT could improve clinical outcomes of patients with IKZF1 mutation ( 43 ). While CREBBP mutation is associated with drug resistance and recurrence in ALL ( 44 , 45 ). The mutation of this gene frequently occurred in childhood ALL and was rare in adults ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…IKZF1 deletion is a critical poor prognostic biomarker in ALL ( 41 ), the mutation of which drives normal lymphocytes to develop into leukemia ( 42 ).It was reported that HSCT could improve clinical outcomes of patients with IKZF1 mutation ( 43 ). While CREBBP mutation is associated with drug resistance and recurrence in ALL ( 44 , 45 ). The mutation of this gene frequently occurred in childhood ALL and was rare in adults ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, isoform 4-specific interactions with factors such as CREBBP and GML that interface with the oestrogen receptor as well as the BRCA1 and p53 tumour suppressors suggest isoform-specific roles in the pathogenesis and treatment of breast cancer [86,120]. By downregulating cell proliferation, SEPT9_i4 may impact the response of cancer cells to chemotherapy as observed with alterations in the expression of CREBBP and GML, which also regulate cell proliferation [69,87]. Of note, SEPT9 isoforms have been implicated in cellular adaptation to anti-cancer drugs [38,41].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in nuclear size reduction was accompanied by an overall reduction in cell size and the growth rates of MCF-7 cells expressing GFP-SEPT9_i4 (Figure S5C and S5E), while cell morphology was not altered as indicated by quantification of cell complexity (ratio of perimeter length to surface area) (Figure S5D). These data suggest that SEPT9_i4 may regulate nuclear size and cell growth by suppressing CREBBP functions in nuclear size and cell proliferation [67][68][69].…”
Section: Differential Interactions Of Sept9 Isoforms With Nuclear Centrosomal and Ciliary Proteinsmentioning
confidence: 99%
“…We subjected the 697 isogenic cell lines to a targeted drug screen, using a wide range of concentrations, focussed on clinically-actionable drugs in classes implicated or hypothesized to show differential sensitivity in published models of B-cell lymphoma and other CREBBP-mutated malignancies (Extended Data Table 1) 3,4,[10][11][12]17,19,20 . CREBBP-mutated 697 cells were not differentially sensitive to traditional cytotoxic chemotherapy, and paradoxically showed a degree of sensitization to the glucocorticoid Dexamethasone, used in current ALL induction regimens (Fig.…”
Section: Crebbp-mutated B-all Shows Increased Sensitivity To Venetoclaxmentioning
confidence: 99%